PEMANFAATAN KOMPOS DAN MIKORIZA UNTUK MEMPERBAIKI KESUBURAN TANAH, PERTUMBUHAN SERTA PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata) - Rajagukguk, Reinhard Novando; Nuraini, Yulia (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Inceptisols dominate Indonesia's land area; therefore, future utilization needs to be maximized, especially land that has undergone extensive tillage continuously. Inceptisols have low levels of essential nutrients, especially nitrogen, phosphorus, and potassium. One of the efforts that can be made to improve nutrient content is the application of compost. This study aimed to investigate the effect of compost combined with mycorrhiza on total N, available P, exchangeable K, and soil organic C, as well as the growth and yield of sweet corn. The experimental design used in this study was a completely randomized design consisting of five treatments with three replications. Each observation parameter was analyzed using the F test at the 5% level. Parameters that significantly affected the F test were followed by the DMRT test at the 5% level. All observed data were tested for correlation using SPSS V24 to see the relationship between observation parameters. The results showed that the application of a combination of compost and mycorrhizae increased total N content by 78.7%, available P by 26.6%, soil organic C by 29.54%, plant height by 143.87cm, number of leaves by 11.33 leaves, and cob weight by 294.33 g compared to control. The correlation test showed that applying a combination of compost and mycorrhiza affected N in the soil, so the growth and yield of corn were higher.